[In the dark ; PNOC ; Komiks relief [videorecording] - Lazaro, Cheche (Quezon City Probe Productions, 1990)
Looks into the four-long hour daily power interruptions in the city ; the causes and prospects for improvement of the electric power and the Geothermal energy source in Mt. Apo in Mindanao run by PNOC ; and a fresh look at Filipino komiks as the number one reading source of Filipino readers.
In the ark (14 min.) -- PNOC (18 min.) -- Komiks relief (16 min.)
VHS.
Keywords: Philippine National Oil Company; Brownouts -- Philippines; Cartoons and comics; Comic books, strips, etc. -- Philippines; Electric power failures -- Philippines; Geothermal power plants -- Philippines -- Mindanao; Petroleum industry and trade -- Philippines; Petroleum products -- Prices